KINETIC EVIDENCE FOR DIRECT ELECTRON-TRANSFER BETWEEN TRIS(4-BROMOPHENYL)-AMMONIUMYL AND THE ACETATE ANION IN ACETONITRILE SOLUTION - Compton, R; Laing, M (1988)
The reaction between tris(4-bromophenyl)ammoniumyl, electrogenerated from the parent amine, and the acetate anion has been studied in acetonitrile solution using rotating disc voltammetry and shown to involve a direct electron transfer reaction, resulting in an EC′ mechanism, in contrast to a previously reported suggestion that acylation of the radical cation was the dominant reaction pathway under these conditions.